Sykepleieres erfaringer med innføring av sykepleiediagnoser - Torunn Hatlen Nøst; Lene Elisabeth Blekken; Beate André (Septentrio Academic Publishing, 2015)
Nurses' experiences with introduction of nursing diagnoses Background: Studies have shown that use of nursing diagnoses can improve quality of documented assessments, quality of described interventions and outcomes, and that they facilitate communication and continuity between practitioners in the health care services. Collaboration between a hospital and a university college was established to study the implementation of nursing diagnoses. Purpose: This study intends to investigate the feasibility of the study and the experiences nurses in clinical practice have after an implementation of nursing diagnoses. Method: A focus group interview with six participants was conducted. The researchers' experiences upon the intervention feasibility were logged as notes. Results: The participants found the intervention helpful and educational, but also frustrating. Nursing diagnoses seems to be useful in clinical work, but the intervention period may have been too short to achieve changes in the documentation work. Conclusion: There is need for further studies so that nursing documentation can be a good tool to support nurses in their working process.